Large trion binding energy in monolayer WS2 via strain-enhanced electron–phonon coupling - Yunus Waheed; Sumitra Shit; Jithin T. Surendran; Indrajeet D. Prasad; Kenji Watanabe; Takashi Taniguchi; Santosh Kumar (Communications Materials)
Abstract Transition metal dichalcogenides and related layered materials in their monolayer and a few layers thicknesses regime provide a promising optoelectronic platform for exploring the excitonic- and many-body physics. Here, we have investigated the effects of nanoparticle-induced local strain on the optical properties of exciton, X 0, and trion, X −, in monolayer WS2. Biaxial tensile strain up to 2.0% was quantified and verified by monitoring the changes in three prominent Raman modes of WS2: $${{{{\rm{E}}}}}_{2g}^{1}$$ E 2 g 1 (Γ), A1g , and 2LA(M). We obtained an increase of 34 meV in X − binding energy with an average tuning rate of 17.5 ± 2.5 meV/% strain across all the samples irrespective of the surrounding dielectric environment of monolayer WS2 and the sample preparation conditions. Strain-induced linewidth broadening and deformation potentials of both X 0 and X − emission elucidate that X − binding energy increases due to strain-enhanced electron–phonon coupling. This work holds relevance for future X −-based nano-opto-electro-mechanical systems and devices.